2018
DOI: 10.3390/en11061423
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Scheduling Dispatch of a Microgrid under Risk Assessment

Abstract: This paper presents the scheduling dispatch of a microgrid (MG), while considering renewable energy, battery storage systems, and time-of-use price. For the risk evaluation of an MG, the Value-at-Risk (VAR) is calculated by using the Historical Simulation Method (HSM). By considering the various confidence levels of the VAR, a scheduling dispatch model of the MG is formulated to achieve a reasonable trade-off between the risk and cost. An Improved Bee Swarm Optimization (IBSO) is proposed to solve the scheduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Financial risk assessment techniques are being increasingly used in the field of power systems to manage renewable energy risks in generation planning and electricity markets [23]. The Markowitz mean‐variance theory [24], value at risk (VaR) [25] and Sortino ratio [22] are examples of financial risk measurement tools that have been tested in power systems. The conditional value at risk (CVaR) is another measure which has performed better than the VaR.…”
Section: Introductionmentioning
confidence: 99%
“…Financial risk assessment techniques are being increasingly used in the field of power systems to manage renewable energy risks in generation planning and electricity markets [23]. The Markowitz mean‐variance theory [24], value at risk (VaR) [25] and Sortino ratio [22] are examples of financial risk measurement tools that have been tested in power systems. The conditional value at risk (CVaR) is another measure which has performed better than the VaR.…”
Section: Introductionmentioning
confidence: 99%
“…Impact on the financial and technical aspects of running the power system under conditions of financial risk based on the behaviour of other players in the market was given in [20] where it was shown that the greatest financial profit of 10498.98 currency units for the case is achieved when the production of the solar power plants and the wind farms is managed under a single aggregator. Two scenarios for the microgrids with RES and electricity storage under the influence of risk are given in [21] where the author specifically considered the rate of change in solar radiation and wind speed between the two time periods, further examining the system's resistance to sudden changes. Operation of the virtual power plant consisted of wind power, solar power, battery and diesel power under the conditions of the financial risks affecting its daily profit were explored in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although optimization methods and control theories are applied in power systems to improve safety and stability [10,11], risks are still inevitable in the operation of the power grids. A generalized concept of risk is the product of the probability and consequences of the contingency.…”
Section: Introductionmentioning
confidence: 99%